Age and Personal Growth at Work. The Moderating Role of Transformational Leadership on Teachers‘ Self-Efficacy and Thriving - Niessen, Cornelia; Mäder, Inge; Schröder, Carina; Volmer, Judith (18th European Association of Work and Organizational Psychology Congress, 2017)

Arbeitsleistung im Kontext von Laufbahnentwicklung - Niessen, Cornelia; Hommelhoff, Sabine; Mäder, Inge (Handbuch Laufbahnmanagement und Karriereplanung, 2018)

How does job insecurity relate to adaptive performance? - Niessen, Cornelia; Mäder, Inge (17th congress of the European Association of Work and Organizational Psychology, 2015)
Niessen, C. & Mäder, I. (2015, May). How does job insecurity relate to adaptive performance?. Paper presented at the 17th congress of the European Association of Work and Organizational Psychology, Oslo, Norway.

Implizite Motive als Prädiktoren von Leader- Member- Exchange: die Rolle von Moderatoren - Mäder, Inge (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2012)

I will stay but I should go: The moderating role of cognitive job crafting in the relationship between turnover intentions, affect and job performance. - Weseler, Daniela; Hommelhoff, Sabine; Mäder, Inge; Niessen, Cornelia (Presentation at the 18th congress of the European Association of Work and Organizational Psychology, Dublin, Ireland., 2017)

Nonlinear associations between job insecurity and adaptive performance: The mediating role of negative affect and negative work reflection. - Mäder, Inge; Niessen, Cornelia (Human performance, 2017)

Resilience and adaptation to organizational change: The moderating role of transformational leadership - Mäder, Inge; Niessen, Cornelia (18th Congress of the European Association of Work and Organizational Psychology Dublin, May 18, 2017, 2017)

Thriving when exhausted: The role of perceived transformational leadership. - Niessen, Cornelia; Mäder, Inge; Jimmieson, N.L. (Journal of Vocational Behavior, 2017)

Thriving when exhausted: The Role of Tranformational Leadership. - Niessen, Cornelia; Mäder, Inge; Jimmieson, N.L. (Poster presented at the 32nd Annual SIOP Conference, Orlando, Florida., 2017)

Uncertainty and adaption to organizational change: The moderating role of leaders` informational support and employees` trust in leaders. - Mäder, Inge; Niessen, Cornelia (European Association of Work and Organizational Psychology Small Group Meeting (SGM). The psychology of organizational change: Understanding and dealing with change recipients’ reactions. Athens, Greece., 2016)